Impacts of forest loss on inland waters: Identifying critical research zones based on deforestation rates, aquatic ecosystem services, and past research effort. (September 2016) - Fugère, Vincent; Nyboer, Elizabeth A.; Bleecker, Johanna C.; Chapman, Lauren J.
Abstract: Deforestation is a major threat to global aquatic biodiversity and ecosystem services. Regional studies are needed to understand and mitigate impacts of deforestation on local inland waters, yet such studies remain unavailable in many regions of the world where the risks of impact are high, for example in the tropics. Our goal was to identify such understudied regions by quantifying and mapping the global research need and effort on deforestation impacts on inland waters. We defined research need based on countries' deforestation rate, fish diversity, and vulnerability of human populations to freshwater ecosystem degradation, the latter estimated from water scarcity and consumption and trade of local freshwater fish. We quantified research effort by reviewing 1362 publications on deforestation and freshwater ecosystems, thereby providing the first quantitative literature review on this important conservation problem. We found that tropical countries exhibited strong overlap among deforestation, freshwater fish diversity, and vulnerability of human populations to freshwater ecosystem degradation, and therefore have high research need relative to temperate regions. However, we found that the best predictor of research effort on deforestation and aquatic systems was the size of a country's economy (indicated by gross domestic product), not research need. Finally, we uncovered a strong research bias against tropical Africa, the only extensive region of the world that has a high research need and a low research effort. This global analysis suggests that future research effort on deforestation impacts on inland waters should try to alleviate existing biases by increasing interregional cooperation and transfer of research resources to regions of high research need and/or low research effort, with a particular focus on the critical research zone that is tropical Africa. Highlights: Research on deforestation impacts on inland waters is most needed in the tropics. Yet, past research effort on this problem has focused on high-GDP temperate areas. Tropical Africa is an especially under-studied yet vulnerable area.